Is One of the Least Coordinating Anions Suitable to Serve as Electrolyte Salt for Magnesium‐Ion Batteries?. Issue 12 (17th October 2022) - Schmidt, Alexei; Koger, Hendrik; Barthélemy, Antoine; Studer, Gauthier; Esser, Birgit; Krossing, Ingo
Abstract: Weakly coordinating anions (WCAs) are considered promising candidates for application as electrolytes in multivalent post‐lithium batteries. One strong candidate as electrolyte salt for Mg battery application is [Mg(L) x ][Al(OR F )4 ]2 (L=MeCN (acetonitrile), DME (1, 2‐dimethoxyethane); x =3, 6; R F =C(CF3 )3 ) that contains [Al(OR F )4 ] − as one of the least coordinating WCAs known. Here we present a novel synthetic route, for which vibrational, NMR and XRD analyses show the formation of a clean, pristine electrolyte salt without the common contaminants found in published synthetic routes. The electrochemistry of this pristine and pure [Mg(DME)3 ][Al(OR F )4 ]2 electrolyte (0.2 m in DME) was investigated via cyclic voltammetry (CV). In contrast to previous publications using impure materials, the CV showed no sign for Mg deposition from the pristine electrolyte for all conditions tested. This also holds when including the additives LiCl, NaCl, MgCl2, Li[BH4 ] or a mixture of MgCl2 /Mg[HMDS]2 (HMDS=hexamethyldisilazide) in THF. Quantum chemical calculations suggested the possibility of anion decomposition at the negative electrode, leading to an electronically insulating MgF2 layer (rutile structure) on all the electrode materials tested. This hypothesis was confirmed by an XPS investigation of electrodes exposed to the electrolytes containing the WCAs [Al(OR F )4 ] − and [Al(OC(H)(CF3 )2 )4 ] − at negative potentials, which only showed the presence of MgF2 for the [Al(OR F )4 ] − electrolyte, but not for the related [Al(OC(H)(CF3 )2 )4 ] − electrolyte (which allowed to deposit magnesium reversibly on the electrode). Abstract : Too much fluorine ? Weakly coordinating anions improve electrolytes for magnesium ion batteries by inhibiting ion‐pairing, increasing the electrochemical window and conductivity. A novel synthetic route towards clean and contaminant‐free [Mg(L) x ][Al(OR F )4 ]2 (L=MeCN, DME; x =3, 6; R F =C(CF3 )3 ), containing [Al(OR F )4 ] − (also called [TPFA] −, [Al(O t Bu F ]4 −, [ pf ] − ) as one of the least coordinating anions, led to surprising electrochemical data, contradicting previously published results using this electrolyte salt in DME solution.